Assessing residents' satisfaction on social housing quality and policy in Batna City, Eastern Algeria - Djafri, Riadh (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
Social housing is an issue of concern for governments all over the world. In Algeria, the issue of housing has been addressed since independence in 1962 where the housing policies implemented in Algeria have raised many discussions. As urban growth has been increasing steadily and given that adequate quality social housing in urban areas is beyond most low-income Algerians. This research investigates and evaluates social housing quality, adequacy, provision and quality of life of the residents of social housing in the city of Batna in eastern Algeria. It explores and examines the interrelationships between variables affecting social housing. The thesis explores the relationship between Socio-economic Characteristics (SEC), Residential Quality and Housing Adequacy (RQHA), Social Housing Provision (SHP), and Residents' Quality of life (RQOL) in the context of social housing in Batna city. A conceptual framework was developed through an extensive review of the literature proposing a total of ten hypotheses. To achieve its objectives, this research adopted a mixed-method design by testing the proposed conceptual framework using primary data collected from a survey of 418 residents. The data were analysed using descriptive analysis and Exploratory Factor Analysis through SPSS. In addition, Confirmatory Factor Analysis was performed using AMOS before validating the measurement model and testing the hypotheses through structural equation modelling as proposed in the conceptual framework. A face-to-face semi-structured interview was conducted with five selected experts. These individuals were selected based on their experience and engagement in areas related to social housing. The interviews were analysed using thematic analysis and coding procedures. Besides that, direct qualitative observation was performed to examine the current physical environment of the study area. This was followed by the analysis of documents obtained from the Housing Department including statistics, maps, photos, and architectural plans. The results revealed that six out of ten hypotheses were supported. RQHA appeared to have a vital role in the conceptual framework as it influences SHP and RQOL and it was influenced by SEC. In addition, RQHA fully mediates the relationship between SEC and SHP, and between SEC and RQOL. The findings of the qualitative interviews revealed three main themes, namely housing policies in terms of quality and quantity, housing adequacy and quality of life, and improvement of social housing quality. Accordingly, a significant change in the structure of the Algerian housing policies is effectively needed to offer decent and adequate housing and to meet the needs of their residents especially in terms of internal and external design, and public spaces. The findings would serve as an instrument to support and guide housing policies. This will ameliorate social housing in terms of its quality, adequacy and provision which will lead to improving the residents' quality of life. The findings contribute significantly to government, housing stakeholders including Offices of Promotion and Real Estate Management, architects, project managers, and urban planners in the context of social housing policymakers, design, planning and construction.